Effect of silica layer on bonding strength of thermoplastic nylon to cold cure acrylic resin - Israa M Hummoudi (College of Dentistry/ University of Baghdad, 2014)
Background: The combination of thermoplastic nylon resin materials and auto polymerizing resin is necessary in some situation for repair and adjustment. This study evaluated shear bond strength between thermoplastic nylon material (flexible) and auto polymerizing acrylic resin subjected to holes and silica coated layer. Materials and Method: Forty five (45) specimens were prepared from flexible acrylic bonded to auto-polymerizing acrylic resin and divided into three groups according to the surface treatments as follows: Group A: 15 specimens of flexible acrylic bonded with cold-cure acrylic by holes. Group B: 15 specimens of flexible acrylic bonded with cold-cure acrylic by silica coated layer. Group C: 15 specimens of flexible acrylic bonded with cold-cure acrylic by combination of holes and silica coated layer. All specimens were analyzed by using Instron testing machine. Results: The result of this study showed that high mean values were obtained from group C (combination) while low mean values were obtained from B (silica coated layer). Conclusion: It can be concluded that combination of mechanical surface treatment resulted in significant improvement in shear bond strength of flexible acrylic bonded with cold cure acrylic